(3eSGFd CHj OGhO GdSLSJGfi ddEeGe CMeO Hf MfHds - (3CMeO Hf eMeO Hf MfHd, CHh YHO Gddg, GdTjHGfqj GdhGFdj,J (B241 (3g` s
(3ChdgG (B:s
(3MOKfG CHh OGhO SdjeGf Hf GdCTYK GdSLSJGfi bGd (B: (3bdJ dGHi YHO Gddg CMeO Hf eMeO Hf MfHd ESJbHGd GdbHdI HGH GdESJLBA s
(3BNQgG (B:s
(3jfJgi HHGH (B( (3HjGf CMGOjK jNJda ajgG (B) s
(3GdfSNI HgG MhGTs
(3HYO GdeSGFd JbjjOGJs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B203 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B96s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdabg GdMfHdjs